The Single Particles, Clusters and Biomolecules and Serial Femtosecond Crystallography instrument of the European XFEL: initial installation. (12th April 2019) - Mancuso, Adrian P.; Aquila, Andrew; Batchelor, Lewis; Bean, Richard J.; Bielecki, Johan; Borchers, Gannon; Doerner, Katerina; Giewekemeyer, Klaus; Graceffa, Rita; Kelsey, Oliver D.; Kim, Yoonhee; Kirkwood, Henry J.; et al.
Abstract : An introduction to the early operational capabilities of the Single Particles, Clusters and Biomolecules and Serial Femtosecond Crystallography (SPB/SFX) scientific instrument at the European X‐ray Free Electron Laser facility is presented. Abstract : The European X‐ray Free‐Electron Laser (FEL) became the first operational high‐repetition‐rate hard X‐ray FEL with first lasing in May 2017. Biological structure determination has already benefitted from the unique properties and capabilities of X‐ray FELs, predominantly through the development and application of serial crystallography. The possibility of now performing such experiments at data rates more than an order of magnitude greater than previous X‐ray FELs enables not only a higher rate of discovery but also new classes of experiments previously not feasible at lower data rates. One example is time‐resolved experiments requiring a higher number of time steps for interpretation, or structure determination from samples with low hit rates in conventional X‐ray FEL serial crystallography. Following first lasing at the European XFEL, initial commissioning and operation occurred at two scientific instruments, one of which is the Single Particles, Clusters and Biomolecules and Serial Femtosecond Crystallography (SPB/SFX) instrument. This instrument provides a photon energy range, focal spot sizes and diagnostic tools necessary for structure determination of biological specimens. The instrumentation explicitly addresses serial crystallography and the developing single particle imaging method as well as other forward‐scattering and diffraction techniques. This paper describes the major science cases of SPB/SFX and its initial instrumentation – in particular its optical systems, available sample delivery methods, 2D detectors, supporting optical laser systems and key diagnostic components. The present capabilities of the instrument will be reviewed and a brief outlook of its future capabilities is also described.